Potensi stenochlaena palustris (burm.f.) bedd. Sebagai Antikanker dalam perawatan kanker mulut - Yuliani Taramalinda, Elizabeth; Sandra, Ferry; Oetomo Roeslan, Boedi (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background : The number of deaths due to cancer nearly reached 10 million in 2020, with approximately 90% of them attributed to oral cancer, which falls under the category of head and neck cancers. S. palustris has potential as a chemopreventive agent due to its secondary metabolites, including flavonoids and alkaloids, which have demonstrated inhibitory effects on cancer cell proliferation and induction of apoptosis. Objective : This research aims to assess the potential extract from S. palustris as an anticancer agent in the treatment of oral cancer. The study involves investigating the inhibitory effects of the extract on cancer cell proliferation and its ability to induce apoptosis. Method: The references for this review were sourced from PubMed, Google Scholar, official reports, and global health organizations' websites using search terms like